Anti-Müllerian hormone levels in nurses working night shifts. Issue 3 (2nd April 2020) - Johnson, Candice Y.; Tanz, Lauren J.; Lawson, Christina C.; Howards, Penelope P.; Bertone-Johnson, Elizabeth R.; Eliassen, A. Heather; Schernhammer, Eva S.; Rich-Edwards, Janet W.
Abstract: Our objective was to examine associations between night shift work and serum anti-Müllerian hormone (AMH) levels. We analyzed 1, 537 blood samples from premenopausal female nurses in the Nurses' Health Study II, assayed for AMH. Rotating or permanent night shifts worked in the two weeks before blood collection and years of rotating night shift work were obtained via questionnaire. We found no associations between recent night shifts or rotating night shift work and AMH. The median difference in AMH was 0.3 (95% CI: -0.4, 0.8) ng/mL for ≥5 versus 0 recent night shifts and -0.1 (95% CI: -0.4, 0.3) ng/mL for ≥6 versus 0 years of rotating night shift work. Although we found no associations between night shift work and AMH, this does not preclude associations between night shift work and fertility operating through other mechanisms.